Ideas and Politics in Modern Britain
XIII, 271 p.
Keywords: An examination of the ideas and politics of modern Britain. It looks at the role and relations of the state and the community it both governs and serves. Topics covered range from the collapse of corporate state Keynesianism, to government investment in universities and science.